2017
DOI: 10.21769/bioprotoc.2247
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Angiogenesis in vitro: Three-dimensional Co-culture of Vascular Endothelial Cells and Perivascular Cells in Collagen Type I Gels

Abstract: Angiogenesis defines the process of formation of new vascular structures form existing blood vessels, involved during development, repair processes like wound healing but also linked to pathological changes. During angiogenic processes, endothelial cells build a vascular network and recruit perivascular cells to form mature, stable vessels. Endothelial cells and perivascular cells secret and assemble a vascular basement membrane and interact via close cell-cell contacts. To mimic these processes in vitro we ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Adapted from the literature ( Auler et al, 2017 ), cells in collagen were fixed with 4% PFA for 2 h before staining. Afterward, the samples were blocked using 5% w/v bovine serum albumin in DPBS for 3 h and subsequently stained with a monoclonal mouse anti-human CD31 primary antibody (1:50) overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Adapted from the literature ( Auler et al, 2017 ), cells in collagen were fixed with 4% PFA for 2 h before staining. Afterward, the samples were blocked using 5% w/v bovine serum albumin in DPBS for 3 h and subsequently stained with a monoclonal mouse anti-human CD31 primary antibody (1:50) overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…A co-culture of EC + PC resulted in complete closure (100%, P < .0001) with apparent immature tubule vessel formation. 32 Following monoculture studies, we observed the effect of EC and/or PC cell contact on NSC migration by culturing NSC with EC, PC, or EC + PC in a 1:1 cell ratio for co-culture (Figure 1A). In the presence of EC, NSC began to cluster, and interestingly, the clusters (GFP + NSC) began migrating toward the scratched area (46.67% ± 3.80 closure, P < .0001), significantly more than NSC alone (25.05% ± 3.95 closure).…”
Section: Ec Promote Nsc Migration and Clusteringmentioning
confidence: 99%